Symmetry breaking polymerization: one-pot synthesis of plasmonic hybrid Janus nanoparticles1. Issue 23 (21st June 2015) - Wang, Yanming; Ding, Tao; Baumberg, Jeremy J.; Smoukov, Stoyan K.
<x xml:space="preserve">Abstract</x> One-pot hybrid plasmonic janus nanoparticles synthesis.